2019
DOI: 10.5812/msnj.96823
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Self-care Education Based on Orem's Model on Self-care Behaviors of Patients with β-Thalassemia Major: A Clinical Trial

Abstract: Background: Thalassemia negatively affects key aspects of life and self-care behaviors. It is essential to promote self-care behaviors in patients with thalassemia in order to improve their functions and mitigate adverse effects. Objectives: In this context, the present study aimed to investigate the effects of self-care education on self-care behaviors of patients with major β-thalassemia based on Orem's model. Methods: This clinical trial investigated 60 patients with major β-thalassemia who had been admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…In a study by Nasresabetghadam et al on Iranian old women with hypertension, education had a significant effect on different self-care behaviors, including medication adherence, weight control, physical activity, and nutrition behaviors (18). In the study by Masinaienejad et al, similar results were found after providing self-care education to patients with β-thalassemia major (19).…”
Section: Discussionmentioning
confidence: 75%
“…In a study by Nasresabetghadam et al on Iranian old women with hypertension, education had a significant effect on different self-care behaviors, including medication adherence, weight control, physical activity, and nutrition behaviors (18). In the study by Masinaienejad et al, similar results were found after providing self-care education to patients with β-thalassemia major (19).…”
Section: Discussionmentioning
confidence: 75%
“…Depression can cause irreparable complications such as the risk of alcohol and drug abuse, non-adherence to treatment, lower than expected quality of life, delay in the treatment process, etc., in hemodialysis patients (25,26).…”
Section: Introductionmentioning
confidence: 99%